Contrasting effects of host identity, plant community, and local species pool on the composition and colonization levels of arbuscular mycorrhizal fungal community in a temperate grassland - Šmilauer, Petr; Košnar, Jiří; Kotilínek, Milan; Šmilauerová, Marie (Blackwell Publishing LTD, 2020)
Arbuscular mycorrhizal fungi (AMFs) are important plant symbionts, but we know little about the effects of plant taxonomic identity or functional group on the AMF community composition. To examine the effects of the surrounding plant community, of the host, and of the AMF pool on the AMF community in plant roots, we manipulated plant community composition in a long-term field experiment. Within four types of manipulated grassland plots, seedlings of eight grassland plant species were planted for 12 wk, and AMFs in their roots were quantified. Additionally, we characterized the AMF community of individual plots (as their AMF pool) and quantified plot abiotic conditions. The largest determinant of AMF community composition was the pool of available AMFs, varying at metre scale due to changing soil conditions. The second strongest predictor was the host functional group. The differences between grasses and dicotyledonous forbs in AMF community variation and diversity were much larger than the differences among species within those groups. High cover of forbs in the surrounding plant community had a strong positive effect on AMF colonization intensity in grass hosts. Using a manipulative field experiment enabled us to demonstrate direct causal effects of plant host and surrounding vegetation.
Keywords: arbuscular mycorrhizal fungi (AMF); diversity; forbs; grasses; host identity effect; microscopy; next-generation sequencing